POTENSI ANTIINFLAMASI EKSTRAK DAUN KECAPI SENTUL (Sandoricum koetjape Merr) DENGAN METODE STABILISASI MEMBRAN SEL DARAH MERAH - Yusrinie Wasiaturrahmah; Nida Amalia (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Tissues that experience detrimental disturbances caused by chemical, mechanical or infectious stimuli will respond in the form of inflammation. Inflammatory processes that cannot be controlled and last long can damage cells, causing pathological effects. Kecapi sentul (Sandoricum koetjape Merr) is a plant that can thrive in Indonesia. Kecapi sentul leaves contain saponins, flavonoids, tannins, alkaloids, steroids, phenolics, and triterpenoids. The content of bioactive compounds in kecapi sentul leaves can provide various pharmacological effects, including as an anti-inflammatory. This study aims to determine the anti-inflammatory potential of kecapi sentul leaf extract using the membrane stabilization of the red blood cell method. The results showed that the percentage value of hemolysis inhibition possessed by kecapi sentul leaf extract at concentrations of 50, 100, 200, and 400 ppm were 6.137%, 15.884%, 24.549%, and 40.433%. The percentage of hemolysis inhibition possessed by 100 ppm aspirin as a positive control was 60.650%. The IC50 value of Kecapi sentul leaf extract was 492.305 ppm. Kecapi Sentul leaf extract is known to have the potential as an anti-inflammatory.